2022
DOI: 10.3390/foods11040591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Physicochemical and Functional Properties of Aquasoya (Glycine max Merr.) Powder for Vegan Muffin Preparation

Abstract: Recent concerns on health and sustainability have prompted the use of legumes as a source of plant-based proteins, resulting in the application of their cooking water as a substitute for egg whites. In this study, the cooking water of yellow soybeans was powdered, and, subsequently, the nutritional and functional characteristics of powders from yellow soybeans (YSP), chickpeas (CHP), and egg whites (EWP) were compared. The main components of these powders (total polyphenol, total carbohydrate, and protein), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Cooking water has already been established as a foaming agent capable of replacing egg white in food preparations (Buhl et al ., 2019; Kim & Shin, 2022). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cooking water has already been established as a foaming agent capable of replacing egg white in food preparations (Buhl et al ., 2019; Kim & Shin, 2022). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that Aquasoya had higher total polyphenol, total carbohydrate, and protein contents, as well as better emulsifying and foaming abilities than aquafaba. Therefore, recent studies have identified ways to apply it to vegan bakery products and further improve their functionality [4][5][6], verifying its potential use in food products as an upcycled ingredient. However, their applicability as an emulsifier into bioactive compounds-formulated oil-in-water (O/W) emulsion systems has yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to this date, the study of the application of the cooking water from legumes has been mainly focused on products such as bread (Huang et al ., 2018), meringue (Lafarga et al ., 2019; Meurer et al ., 2020), cakes (Mustafa et al ., 2018; Aslan & ErtaŞ, 2020; Kim & Shin, 2022) and mayonnaise (Raikos et al ., 2019; He et al ., 2021c) while functional properties such as gelling, thickening and binding have not been thoroughly studied. Consequently, it is necessary to explore more food products that can incorporate cooking water from legumes as a functional ingredient in their formulation.…”
Section: Introductionmentioning
confidence: 99%
“…One of these by‐products is the water that is discarded after the cooking of legumes. The cooking water from legumes has proven to have remarkable foaming and emulsifying properties capable of replacing egg in mousse (Damian et al ., 2018), mayonnaise (Raikos et al ., 2019; He et al ., 2021c), bread (Huang et al ., 2018; Shim et al ., 2021), meringue (Lafarga et al ., 2019; Meurer et al ., 2020) and cakes (Mustafa et al ., 2018; Aslan & ErtaŞ, 2020; Kim & Shin, 2022). These functional properties are a result of the composition of the cooking water which typically corresponds to low molecular weight proteins, simple carbohydrates and other minor components such as phenolic compounds, saponins and coacervates (He et al ., 2021a).…”
Section: Introductionmentioning
confidence: 99%